Giant solitary fibrous tumors of the liver. A case report in Argentina - Almanzo, Santiago; Varela, Estanislao; Montes, Leonardo A.; Santilli, Juan P.; Barros Schelotto, H. Pablo; Gondolesi, Gabriel E. (Revista Argentina de Cirugía, 2021)
Solitary fibrous tumors of the liver are uncommon benign tumors originating from the submesothelial tissue with non-well-defined malignant potential. Most cases present as asymptomatic, some cases show abdominal bloating and a palpable mass. They may mimic other tumors on imaging tests and surgery is indicated. We report a case of a 70-year-old female patient treated with left lateral liver resection with literature review of the condition.